2016
DOI: 10.25268/bimc.invemar.2004.33.0.251
|View full text |Cite
|
Sign up to set email alerts
|

Condición Actual De Las Formaciones Coralinas De Acropora Palmata Y A. Cervicornis en El Parque Nacional Natural Tayrona (Colombia)

Abstract: To assess the status of coral formations dominated by A c ro p o r a palmata (APF) and A. cervicornis (ACF) in the Tayrona National Natural Park (TNNP), Colombian Caribbean, a study was conducted at the bays of Chengue, Gayraca, Nenguange and Cinto between May- December 2001. The distribution and extension of the formations in the study area were evaluated by swimming along the coast and using draft maps, a GPS and a calibrated flow-meter, and their living cover were estimated in quadrat-belt transects (1x10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 12 publications
0
23
0
17
Order By: Relevance
“…obs., 2010). Additionally, Chengue Bay comprises a highly developed mangrove ecosystem (Garzón-Ferreira & Cano, 1991) which may serve as nursery for lionfish larvae and juveniles. This is further supported by the study of Arbeláez & Acero P (2011), who found lionfish juveniles of 3–10 cm lengths at the submerged roots of the mangroves bordering the entrance to the southern lagoon in Chengue Bay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…obs., 2010). Additionally, Chengue Bay comprises a highly developed mangrove ecosystem (Garzón-Ferreira & Cano, 1991) which may serve as nursery for lionfish larvae and juveniles. This is further supported by the study of Arbeláez & Acero P (2011), who found lionfish juveniles of 3–10 cm lengths at the submerged roots of the mangroves bordering the entrance to the southern lagoon in Chengue Bay.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, juvenile P. volitans (3–10 cm lengths) were observed in the mangrove ecosystem of Chengue Bay (Arbeláez & Acero P, 2011). The ecological consequences of lionfish are of particular interest for the TNNP area due to its major coastal biodiversity (Garzón-Ferreira & Cano, 1991). The TNNP is a fishing restricted area administrated by the National Natural Parks of Colombia dealing with all territories of marine parks and reserves.…”
Section: Introductionmentioning
confidence: 99%
“…palmata is confined to shallow areas exposed to high swells (Garzón‐Ferreira et al . ), encrusting sponges should be dominant on this species. By contrast, vertical growth of sponges is more likely on Ac.…”
Section: Discussionmentioning
confidence: 92%
“…Then, from 1980 onwards, a drastic decline occurred in these species throughout the entire Caribbean attributed to white band disease (Garzón‐Ferreira et al . , ). Mortality rates of 60% for Ac.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation